Criminal Liability of Child Exploitation Through TikTok Live Streams in Orphanage Foundations (A Case Study of Decision Number 148/Pid.Sus/2024/PN Mdn) - Juniawaty, Tata Adela; Harefa, Beniharmoni (JURNAL MERCATORIA, 2024)
The helplessness of children in protecting themselves provides opportunities for adults to exploit them. As in Decision Number 148/Pid.Sus/2024/PN Mdn, where the development of digitalization and social media trends, namely TikTok, was misused as a means of exploiting children in foster care. The perpetrators take advantage of children's vulnerability by having the child appear in TikTok live streaming to attract audience sympathy in order to get gifts that can be converted into money. This study aims to analyze the guarantee of legal protection for orphanage children as victims of exploitation and examine the criminal liability of the manager of the orphanage foundation in cases of child exploitation through TikTok live streaming. The normative juridical method with a statutory approach and a case approach is used in this research. The results show that orphanage children who are victims of exploitation are entitled to legal protection guarantees in the form of special protection, social rehabilitation, legal assistance, and supervision by empowerment institutions such as KPAI. The actions of the orphanage manager are proven to meet the requirements of criminal liability because they intentionally exploit for material gain, have the ability to be responsible, and without any excuse that can eliminate criminal responsibility.